(untitled) (Journal of Numerical Optimization and Technology Management, 2024)
Universities are the backbone of a country’s development. Public universities are subsidised by the government, with funds coming from taxpayers’ contributions. It is therefore important that public universities utilise their resources efficiently. This study evaluates the performance of five academic departments for the period 2016-2018. The tool used to evaluate efficiency is Data Envelopment Analysis (DEA) with CCR output-oriented model using a software DEA-Solver-LV version 8. The secondary data of the three input variables are the number of academic staff, the number of non-academic staff and capital grants. The three output variables used in this study are the number of publications, the number of PhD students and the number of undergraduate graduates. The results show that the departments that are really efficient in the years 2016 to 2018 are the academic departments B and E. The average efficiency score from 2016 to 2018 is 0.972436, 1.0000 and 0.990989, respectively, which shows that the performance of departments in general has been somewhat inconsistent over the three years.